PENERJEMAHAN AL-QURAN BERBAHASA MANDAR KARYA M. IDHOM KHALID BODI: TELAAH KONTEN - M. Pudail (Wahana Islamika: Jurnal Studi Keislaman, 2017)
This study uses literature, the research is carried out by tracing and examining the literature as a qualitative study and conducting interviews directly with the authors of the Qur'anic Translation in Mandar Language as well as the parties involved in this study, in order to support and strengthen existing data . In data collection is done by distinguishing between primary and secondary data. Primary data is the object of this study, namely the Qur'anic Translation in Mandar Language by M. Idham Khalid Bodi. While secondary data are books of the Qur'an, the art of translating, as well as the Mandar books which enrich the subject such as, Dictionary of Mandar Language, Mandar Grammar, Mandar History. The results of this study can be described that the translation methodology used by Idham in his work is that he translates the Qur'an into Mandar language not literally absolutely nor in absolute meaning because sometimes he gives sufficient explanation directly to the form in parentheses rather than footnotes. In his translation Idham has not been fully consistent in using the Mandar language, this can be found in the non-uniformity of the language used, the writing of Mandar letters which should be in accordance with phonology/speech but sometimes forgotten, then the use of various dialects